Залучення спеціалістів до слідчого експерименту на досудовому розслідуванні - Юхно, О. О.; Yukhno, O. O.; Матюшкова, Т. П.; Matiushkova, T. P.; Олександр Юхно (Наше право. – 2022. – № 2. – С. 74-83, 2022)
В статті визначені сучасні теоретичні, законодавчі і прикладні проблемні питання тактики слідчого експерименту та шляхів їх вирішення в частині залучення спеціалістів з різних галузей знань при його підготовці, проведенні та фіксації. Здійснено порівняльний аналіз відповідних положень чинного КПК України, КПК України 1960 року, підзаконних нормативно-правових актів. Викладені особливості взаємодії слідчого, дізнавача, прокурора зі спеціалістами під час їхньої участі у окремих слідчих (розшукових) діях на досудовому розслідуванні окремих видів злочинів. Визначені актуальні напрями подальших досліджень залучення спеціалістів до слідчого експерименту.

Current theoretical, legislative and applied issues of tactics of the investigative experiment and ways to solve them in terms of involving specialists from different fields of knowledge in its preparation, conduct and recording are identified in the article. A comparative analysis of the relevant articles of the current CPC of Ukraine, the CPC of Ukraine of 1960, bylaws, including departmental ones, has been done. It was established that after the renaming of the positions of forensic inspectors (forensic technicians) to forensic specialists, departmental legal acts were not brought into line. The legal bases, proсedural rules and tactical features of involvement of forensic specialists and other specialists into the investigative experiment are determined. The issues of cooperation between investigators, prosecutors, police coroner, with the specialists in various science fields within their participation in the investigative experiment during pre-trial investigation of certain type of criminal offenses have been conducted. The question of the expediency of amendments to the current CPC of Ukraine to anticipate cases of mandatory participation of specialists in the investigative experiment has been raised. It is shown that the forensic specialists involved in the investigative experiment, firstly, act as specialists with special forensic knowledge and skills, and secondly, as members of the investigative team have to follow the instructions of the investigator, coroner, and prosecutor, to assist them during the reconstruction of the crime scene and to record the results of the investigative experiment. The current tendencies for further research on the involvement of specialists into the investigative experiment are determined, such as the involvement of specialists in psychology, as well as specialists and experts of the International Criminal Court in documenting war crimes in Ukraine.

В статье определены современные теоретические, законодательные и прикладные проблемные вопросы тактики следственного эксперимента и пути их решения в части привлечения специалистов из разных областей знаний при его подготовке, проведении и фиксации.
Keywords: залучення спеціалістів; involvement of specialists; слідчий експеримент; спеціаліст-криміналіст; взаємодія; вдосконалення тактики; investigative experiment; forensic specialist; привлечение специалистов; cooperation; improvement of tactics; следственный эксперимент; специалист-криминалист; Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации